Microplastic contamination in Heterotrigona itama bee products (Honey, Pollen, Propolis) from Meratus Geopark, South Kalimantan - Kadarsah, Anang; Putra, Aminuddin Prahatama; Nurliani, Anni; Suhartono, Eko (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
Microplastic pollution has become a significant environmental concern, with recent studies detecting microplastics in various ecosystems and natural products, including those produced by bees. This study investigates the presence, morphology, and distribution of microplastics in products of the stingless bee Heterotrigona itama—specifically honey, pollen, and propolis—collected from six meliponiculture sites within the Meratus Geopark, South Kalimantan, Indonesia. Samples were analyzed using stereomicroscopy to identify microplastic types, quantify particles, and measure sizes. The findings reveal that fibers and fragments are the predominant microplastic forms, with urban locations exhibiting higher contamination levels (approximately 309 to 318 particles per 100 ml) compared to rural areas. Notably, one rural site recorded the highest contamination level (approximately 362 particles per 100 ml), suggesting that factors beyond urbanization, such as agricultural practices and atmospheric deposition, contribute to microplastic pollution. The study underscores the role of bees as natural bioindicators for environmental monitoring and highlights the potential risks of microplastic contamination to bee health, food safety, and ecosystem sustainability. These insights are aligned with Sustainable Development Goal 12, which advocates for responsible consumption and production.